The Effect of the Effective Corporate Tax Rate Toward Investment Decision in Indonesian Public Company - Yasinta Wahyu Pratiwi; Khoirunurrofik (Journal of Indonesian Applied Economics, 2023)
Purpose This research aimed to determine the effect of the effective tax rate in public company investment in Indonesia. Design/methodology/approach The research was conducted using firm data during 2008-2020 and considered the long-term investment concept. Meanwhile, the cross-section of 672 companies and the ordinary least square technique were used to get the estimation. Findings The estimation result showed that the effective tax rate has significant negative effect on fixed asset investment. If effective tax rate decrease, it can be because the company gets tax rate reduction incentives, conduct accelerated depreciation, fiscal reconciliation on the financial statement which can increase fixed asset investments. Moreover, the estimation also showed that the age of the company is able to strengthen the relationship between effective tax rate and company investment. The difference in domestic and foreign companies does not affect the elasticity ETR toward investment. Research limitations/implications                            Based on the estimation result mentioned, it is expected to provide guidance in implementing incentive tax, which can encourage public company investment. Originality/value There are many studies on the effect of income tax rates, but the results cannot be used specifically in Indonesia since the tax sensitivity may be different based on the development level of the country and the characteristics of the company.